Pengembangan Aplikasi Kehadiran Mahasiswa Berbasis Web Pada Program Studi Pendidikan Teknologi Informasi dan Komputer - Ferry Marlianto; Dewi Sulistiyarini; Febrianto Sabirin (Universitas Negeri Padang, 2020)
Through Aplikasi Kehadiran Mahasiswa Teknologi Informasi dan Komputer (AKEMATIK), Education of Technology Information and Computer Program on IKIP PGRI Pontianak can facilitate lecturers in filling teaching journals and monitoring student attendance, while also helping to prepare lecture reports that will help evaluation of teaching and learning in the Program Studi P.TIK IKIP PGRI Pontianak. The research aims to: 1) provide an overview of the application development process; and 2) find out the feasibility of the application. Application development uses the ADDIE model which consists of 5 stages: 1) Analysis; 2) Design; 3) Development; 4) Implementation; and 5) Evaluation. Based on this model it is known that the application has 3 actors namely admin, lecturer, and student. Application testing is done by validating media experts, and alpha testing. The results of expert validation were in the excellent category. The alpha test was conducted on 15 lecturers and 30 students of P.TIK, the results were in the excellent category.